Factors Related To Compliance With Diet Management In Outpatient Patients With Type 2 Diabetes Mellitus In Sibolga City 2020 - Crishartanto Simanungkalit; Devi Kristina Hutagalung; Ririn Manalu (Institute of Computer Science (IOCS), 2020)
Management of type 2 diabetes includes meal planning or diet, physical activity, blood sugar control, and taking medication. The prevalence of type 2 DM cases reaches 85-90%.The type of research used is a cross sectional study with a population of all patients with type 2 DM in 2020 and the sample size is 57 respondents. Measurement of diet management was carried out using a questionnaire.The results showed that there was a relationship between age (p < 0.01), gender (p < 0.01), and family roles (p: <0.01) with adherence to the dietary management of type 2 diabetes. There was no relationship between education (p: 0.44), occupation (p: 0.7), knowledge (p: 0.42), and the role of health workers (p: 0.7). Factors related to adherence in the management of type 2 diabetes diet are age, gender, and family roles.